Teaching Voiced and Voiceless Sounds in EFL Classrooms: A Conceptual Review of Challenges and Pedagogical Strategies - Aswar Aswar; Abdul Rahman R. (Jurnal Ilmiah Multidisiplin Amsir, 2026)
The teaching of pronunciation, particularly the distinction between voiced and voiceless sounds, remains a critically underexplored domain within English as a Foreign Language (EFL) pedagogy. This article presents a conceptual review grounded in three theoretical pillars: phonological theory, first language (L1) transfer theory, and intelligibility-based pronunciation instruction. Three primary challenges are identified: L1 phonological interference, articulatory and perceptual difficulty, and limited phonological awareness among learners and teachers. Four evidence-based pedagogical strategies are proposed: explicit phonological instruction, minimal pair practice embedded in communicative tasks, auditory discrimination training, and technology-assisted pronunciation tools. The article argues that the intelligibility principle should guide instructional priorities, with high-functional-load contrasts such as /s/–/z/, /t/–/d/, and /f/–/v/ receiving primary attention. Implications are drawn for EFL teachers, curriculum designers, and teacher training programs.